KOMPOSISI FISIK KARKAS BROILER YANG DIBERIKAN CAMPURAN SARI KUNYIT (Curcuma domestica Val.) DENGAN MADU (Apis sp.) MELALUI AIR MINUM - Pratama I. G. N. A. W.; I. P. A. Astawa; D. A. Warmadewi (Fakultas Peternakan Universitas Udayana, 2025)
Turmeric is known to have antibacterial and antioxidant properties, while honey contains antimicrobial and immunostimulant compounds that have the potential to increase the growth and quality of broiler carcasses. This study aims to evaluate the Physical Composition of Broiler Carcasses Given a Mixture of Turmeric Juice (Curcuma domestica Val.) With Honey (Apis sp.) Through Drinking Water. The study used a completely randomized design (CRD) consisting of four treatments and five replications. The treatments consisted of P0 = 0% mixture of turmeric juice and honey, P1 = 1% mixture of turmeric juice and honey, P2 = 2% mixture of turmeric juice and honey, and P3 = 3% mixture of turmeric juice and honey. The variables observed included carcass weight, carcass percentage, meat percentage, bone percentage, and fat and skin percentage. The results showed that the administration of a mixture of turmeric juice with honey had an effect on broiler carcass variables. The highest broiler carcass weight in treatment P2 was (1671.00g/head). The highest carcass percentage was also found in P2 (81.07%), significantly different between treatments (P>0.05), the highest meat percentage was found in P2 (59.91%), but not significant (P>0.05). The lowest bone percentage was found in P2 (28.93%), with a non-significant difference (P>0.05). The lowest subcutaneous fat percentage including skin was also found in P2 (11.16%), but the difference was not significant (P>0.05). The conclusion of this study is that giving a mixture of turmeric juice and honey through drinking water as much as 2% can improve the physical composition of broiler carcasses. ABSTRAK Kunyit dikenal memiliki sifat antibakteri dan antioksidan, sementara madu mengandung senyawa antimikroba dan imunostimulan yang berpotensi meningkatkan pertumbuhan dan kualitas karkas broiler. Penelitian ini bertujuan untuk mengevaluasi komposisi fisik karkas broiler yang diberikan campuran sari kunyit (Curcuma domestica Val.) dengan madu (Apis sp.) melalui air minum. Penelitian menggunakan rancangan acak lengkap (RAL) terdiri dari empat perlakuan dan lima ulangan. Perlakuan terdiri dari P0= 0% campuran sari kunyit dan madu, P1= 1% campuran sari kunyit dan madu, P2= 2% campuran sari kunyit dan madu, dan P3= 3% campuran sari kunyit dan madu. Variabel yang diamati meliputi berat karkas, persentase karkas, persentase daging, persentase tulang, dan persentase lemak dan kulit. Hasil penelitian menunjukkan pemberian campuran sari kunyit dengan madu berpengaruh terhadap variabel karkas broiler. Berat karkas broiler tertinggi perlakuan P2 sebesar (1671,00g/ekor). Persentase karkas tertinggi juga ditemukan pada P2 (81,07%), berbeda nyata antar perlakuan (P>0,05), persentase daging tertinggi terdapat pada P2 (59,91%), namun tidak signifikan (P>0,05). Persentase tulang terendah ditemukan pada P2 (28,93%), dengan perbedaan yang non signifikan (P>0,05). Persentase lemak sub kutan termasuk kulit terendah juga terdapat pada P2 (11,16%), tetapi perbedaannya tidak signifikan (P>0,05). Kesimpulan dari penelitian ini adalah pemberian campuran sari kunyit dengan madu melalui air minum sebanyak 2% mampu memperbaiki komposisi fisik karkas broiler.